Effect of Study Leave Grant Pay on Staff Career Advancement at Code of Conduct Bureau, Abuja - Onuora, Chinasa Maryprudence; Itodo , Sylvanus Mohammed; Anayo, Ezeh Ann (Kashere Journal of Politics and International Relations, 2024)
This study examines the effect of study leave grant payments on staff career advancement in the Code of Conduct Bureau in Abuja. The study aims to assess the influence of study leave grants on the career advancement of staff within the Code of Conduct Bureau in Abuja; and investigate the impact of factors including the availability, accessibility, and utilisation of study leave grants on the career progression and job performance of employees in the Code of Conduct Bureau in Abuja. Survey research design was adopted, with a total strength of 301 staff and 172 sample size, Expectancy Theory, developed by Victor Vroom, was adopted as the framework, the findings revealed that majority of respondents attested study leave grants have significantly improved job satisfaction and motivation in the Code of Conduct Bureau, Abuja. These grants have provided access to professional development opportunities, thereby positively impacting career progression and job performance, thereby enhancing the overall performance of the Bureau. Among the recommendations was that given the positive effect of study leave grants on employee skill development and job performance, it is recommended that the Code of Conduct Bureau, Abuja, consider expanding and diversifying the range of professional development opportunities available to its employees.